Specific Features of Journalism Genres - Shukurova Nigora Shavkatovna (Genius Journals, 2021)
The issue of genre classification, or the system of genres of journalism (its typology), remains one of the most complex and confusing ones so far. In this article, from the point of view of a philosophical and anthropological approach and using "Synergetic method" and an attempt to understand the main theoretical difficulties of the genre classification of journalism will be proposed.
Keywords: Existential theory of journalism; genre; fiction; journalism